2016
DOI: 10.4137/cpath.s39925
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Immune Responses by Exosomes Derived from Antigen-Presenting Cells

Abstract: Exosome-mediated signaling is important in mediating the inflammatory response. To exert their biological or pathophysiological functions in the recipient cells, exosomes deliver a diverse array of biomacromolecules including long and short coding and non-coding RNAs, proteins, and lipids. Exosomes secreted by antigen-presenting cells can confer therapeutic benefits by attenuating or stimulating the immune response. Exosomes play a crucial role in carrying and presenting functional major histocompatibility pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 89 publications
0
67
0
1
Order By: Relevance
“…A previous study showed that HSP70 plays a critical role in liver IR injury [15]. During kidney ischemia, CD11c+ dendritic cells and/or F4/80+ macrophages are the main source of HSP70 expression [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that HSP70 plays a critical role in liver IR injury [15]. During kidney ischemia, CD11c+ dendritic cells and/or F4/80+ macrophages are the main source of HSP70 expression [29].…”
Section: Resultsmentioning
confidence: 99%
“…Reportedly, exosomes derived from antigen-presenting cells activate T and B cells and have been explored for their immune-stimulatory properties in cancer therapy. The immunosuppressive properties of exosomes derived from macrophages and DCs reduced inflammation in animal models of several inflammatory disorders [15, 34]. In autochthonous hepatocellular carcinoma mouse models, DEXs treated in the tumor microenvironment reduced the number of Tregs and the serum concentrations of IL-10 and TGF-β [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DC-derived exosomes also serve as a communication tool with other immune cells such as T cells and B cells (47).…”
Section: The Immunization With Dcs Also Resulted In Enhanced Productimentioning
confidence: 99%
“…Exosomes generated by immune cells have been studied extensively. For instance, exosomes from antigen-presenting cells including dendritic cells (DCs), B cells, and macrophages carry surface MHCI and MHCII molecules and thus directly stimulate CD8 + and CD4 + T cell responses, respectively [15,35]. Besides, Okoye et al demonstrated that Let-7d-containing exosomes derived from primary regulatory T cells (Tregs) inhibited Th1 cell responses by targeting Cox-2 in a mouse model of colitis [36].…”
Section: Introductionmentioning
confidence: 99%